Physiological processes induced by different types of physical activity that either oppose or enhance postprandial glucose tolerance - Hamilton, Marc T.; Hamilton, Deborah G.; Zderic, Theodore W. (Frontiers in Endocrinology, 2025)
Herein, we describe overlooked/misunderstood physiological processes (beyond contraction-induced skeletal muscle insulin sensitivity that is already well appreciated) that either oppose or enhance glucose tolerance during distinct types of acute physical activity. This includes multiple mechanisms both within and outside of muscle. We describe the processes and physiological principles to help explain why postprandial glucose tolerance is often not improved after acute bouts of exercise, or when interrupting prolonged sitting with either brief physical activity breaks or more prolonged standing. We also describe results from a specialized type of soleus muscle activity that is specifically well-geared to amplify and sustain oxidative muscle metabolism for long periods of time when sitting, with evidence that this has meaningful positive effects on systemic glucose and lipid regulation. Methods capable of elevating oxidative muscle metabolism could be advantageous to complement other lifestyle and pharmacological approaches whose mechanisms of action are limited to non-oxidative metabolic pathways. There is much potential need for inducing more oxidative muscle metabolism, because the entire musculature normally accounts for only about 15% of the oxidative metabolism of glucose when sitting inactive, despite being the body’s largest lean tissue mass. A clear understanding of the multiple integrative processes that either tend to attenuate or amplify blood glucose excursions in the postprandial period is significant, given the strong influence of glucose tolerance on healthy aging and prevention of multiple chronic diseases.